Comparative analysis of reinsurance markets in the EAEU countries - Vorobyeva, S.M. (BUKETOV BUSINESS REVIEW, 2023)
Objective: Identification of the state of modern reinsurance markets in the EAEU countries and justification of the possibilities of expanding the total reinsurance capacity within this integration association. Methods: In the study of the issue, both general scientific methods of cognition were used, such as historical and logical methods, analysis and synthesis, induction and deduction, method scientific abstractions, the use of analogies, and empirical methods of cognition such as description and comparative analysis. Findings: Based on the comparative analysis of national reinsurance practices, the specifics of regulatory norms in the organization and conduct of reinsurance in each of the EAEU countries were identified. Special attention is paid to those legislative requirements that significantly hinder the development of a common reinsurance space. The results of this study can be applied in the work of the Eurasian Economic Commission in the development of proposals for the further development of the integration of the financial markets of the EAEU countries. Conclusions: In the context of sanctions restrictions from the United States and European countries, urgent development of measures is needed to form a common reinsurance capacity in the EAEU, which will significantly reduce the dependence of the EAEU countries on international reinsurers and expand the volume of reinsurance operations for each of the Union countries. To achieve this goal, it is necessary to maximize the internal capacities of national insurance markets through the establishment of state reinsurance organizations, the use of mutual reinsurance technologies, the creation of insurance and reinsurance pools. To form a common reinsurance capacity of the EAEU countries, along with the creation of a superstructure reinsurance organization, the author proposed the creation of a reinsurance pool by state reinsurers of the countries of the integration association.